Meta‐analysis on the interrelationship between sarcopenia and mild cognitive impairment, Alzheimer's disease and other forms of dementia - Nadjia Amini; Mounir Ibn Hach; Laurence Lapauw; Jolan Dupont; Laura Vercauteren; Sabine Verschueren; Jos Tournoy; Evelien Gielen (Wiley, 2024)
Abstract Sarcopenia has been associated with adverse health outcomes, including cognitive dysfunction. However, its specific interrelationship with neurocognitive disorders such as mild cognitive impairment (MCI), Alzheimer's disease (AD) or other types of dementia has not been thoroughly explored. This meta‐analysis aims to summarize the existing evidence on this interrelationship. This systematic review was pre‐registered on PROSPERO (CRD42022366309) and reported according to the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses 2020 guidelines. Databases, including PubMed, Embase, CINAHL, Scopus, Web of Science, PEDro, SPORTDiscus and the Cochrane Central Register of Controlled Trials, and the data registry ClinicalTrials.gov were searched from inception to 8 June 2023. Observational studies (cross‐sectional and cohort) and interventional studies reporting on the association and prevalence of sarcopenia in MCI, AD or other types of dementia in adults ≥50 years were included. For the meta‐analysis, pooled odds ratios (OR) with 95% confidence intervals (CI) were calculated for the association of sarcopenia with the neurocognitive disorders using random‐effects/fixed‐effects models. Subgroup analyses were performed to identify potential sources of heterogeneity. A total of 77 studies consisting of 92 058 subjects were finally included in the qualitative analysis (71 cross‐sectional, 4 cohort and 2 interventional studies). Studies were heterogeneous, using different diagnostic criteria to define both sarcopenia and cognitive status. The majority of studies (n = 38) included Asian community‐dwelling older adults. Most studies investigated the association of sarcopenia with AD (33/77) and MCI (32/77). For studies focusing on other forms of dementia, two studies included Lewy body dementia and one study included Parkinson's dementia, whereas the remaining studies did not specify dementia aetiology (n = 21). Three cohort studies explored the association between sarcopenia and incident MCI, whereas only one cohort study explored the association between dementia and incident sarcopenia. Two interventional studies investigated whether an exercise programme could prevent the progression of sarcopenia in older adults with dementia or AD. The information for the meta‐analysis was extracted from 26 studies. Sarcopenia was significantly associated with MCI (pooled OR = 1.58, 95% CI 1.42-1.76) (n = 14), AD (pooled OR = 2.97, 95% CI 2.15-4.08) (n = 3) and non‐AD dementia (pooled OR = 1.68, 95% CI 1.09-2.58) (n = 9). The significance and magnitude of the associations differed in subgroup analyses by study design, population, definition of sarcopenia or used tool to measure cognitive status. This meta‐analysis showed that sarcopenia is significantly associated with MCI, AD and other types of dementia. These findings suggest the importance of early screening and prevention of sarcopenia in older people with cognitive dysfunction, although further longitudinal research is needed to clarify the causal relationship.